Neptune’s domain: a political geography of the sea - Glassner, M.I. (Neptune’s Domain: A Political Geography of the Sea, 2024)
First published in 1990, Neptune’s Domain is organized around one unifying theme: the geographic aspects of the new Law of the Sea as expressed primarily in the United Nations Convention on the Law of the Sea. The first two chapters provide essential background information. Chapters 3 through 9 explain relevant provisions of the Convention. The next two chapters cover topics excluded from the Convention, and the last three chapters are more analytical and future-oriented. All students and scholars concerned with the human use of the marine environment will welcome this book, whether they be geographers, political scientists or lawyers. © Martin Ira Glassner 1990. All rights reserved.
Keywords: dept.egm

Thinking outside the ocean-climate nexus: Towards systems-informed decision making in a rapidly changing world - Germond-Duret, Celine; Germond, Basil; Katsanevakis, Stelios; Kelly, Miriah R.; Mazaris, Antonios D.; McKinley, Emma (Science of The Total Environment, 2024)
Despite repeated calls for more inclusive practices, approaches used to address current challenges within the ocean-climate nexus do not sufficiently account for the complexity of the human-social-ecological system. So far, this has prevented efficient and just decision-making and policies. We propose to shift towards systems-informed decision making, which values transdisciplinary system-thinking and cumulative impact assessments, and encourages multi-system collaboration among decision-makers in order to address the recurring technicality of policies and to foster just solutions that account for the needs of varied actors across the sustainable development spectrum.
Keywords: dept.egm; peer-reviewed